2013
DOI: 10.7567/apex.6.015801
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Spin-Polarized Photocathodes Using a GaAs/GaAsP Strain-Compensated Superlattice

Abstract: We have successfully developed a transmission-type GaAs/GaAsP strained superlattice (SL) photocathode, and a high spin-polarization (SP) (90%) with a super-high brightness (~10 7 A⋅cm −2 ⋅sr −1 ) of electron beam was achieved [1]. In this study, we report the design and fabrication of an optimized transmission-type photocathode with strain-compensated SL for higher quantum efficiency (QE).In the GaAs/GaAsP strained SL, a compressive strain was introduced in the GaAs well layers to obtain a large band-splitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
1
14
0
3
Order By: Relevance
“…Figure depicts comparison of QE and polarization. All results show that the polarization is inversely proportional to QE, in accordance with the results of Jin et al Thus, it can be simply stated that the increase in polarization is always achieved at the expense of QE. However, it must be pointed out that reducing the polarization does not necessarily increase the QE.…”
Section: Resultssupporting
confidence: 89%
“…Figure depicts comparison of QE and polarization. All results show that the polarization is inversely proportional to QE, in accordance with the results of Jin et al Thus, it can be simply stated that the increase in polarization is always achieved at the expense of QE. However, it must be pointed out that reducing the polarization does not necessarily increase the QE.…”
Section: Resultssupporting
confidence: 89%
“…3 Strain compensated super-lattice structures are used to improve crystal growth and achieve higher quantum efficiencies in photocathode diodes. 4 The continuous scaling of the active regions of these devices requires characterization techniques with nanometer scale resolution to assist the development of new material processing methods.…”
mentioning
confidence: 99%
“…It has been reported that a GaAs/GaAsP strain-compensated SL could provide a high spin-polarization of over 90%. 4 We first investigated the strain state of the heterostructure using atomic-resolution HAADF-STEM coupled with geometric phase analysis (GPA). 14,21 Figure 1(b) displays the HRSTEM image of the bottom part of the active device region.…”
mentioning
confidence: 99%
“…Using a strained layer superlattice structure and circularly polarized light irradiation with a near band gap energy, highly spin-polarized electrons can be selectively excited up to the conduction band with a low kinetic energy, and extracted through the NEA surface to the vacuum. GaAs/GaAsP superlattice photocathodes with NEA surfaces provide a high spin-polarization of over 90%, 1,2 and are thus being applied to spin-polarized low-energy electron microscopy (LEEM) 3 and spin-polarized transmission electron microscopy (TEM), 4 and are expected to be employed for the international linear collider.…”
Section: Introductionmentioning
confidence: 99%